1963
DOI: 10.1021/jo01046a020
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Metal Chelates. VI.1,2 The Synthesis and Reactions of a Stable Chelate Diazonium Salt3

Abstract: A monoamine derivative L of chromium(III) acetylacetonate has been prepared by reduction of a mononitro derivative I. The chelate amine L was" transformed into a stable chelate diazonium fluoroborate N. The diazonium salt was converted into a monofluoro chelate O. Nitration of mono-and dichloro chromium acetylacetonates afforded a series of chloro-, nitro-substituted chelates. Apparent displacement of chloro by nitro was observed during nitration of the dichloro chelate C.Recent reports from this and other lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1964
1964
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The reliable nitration procedures reported by them have been formalized as standard methods by inclusion in "Inorganic Syntheses" (5). In all cases reported (3,5,6), the method involves the following steps 1) generation of the nitrating agent (presumably acetyl nitrate) by stirring finely ground copper nitrate with acetic anhydride at 0°C for 15 min…”
Section: Chromium (I Ii)mentioning
confidence: 99%
“…The reliable nitration procedures reported by them have been formalized as standard methods by inclusion in "Inorganic Syntheses" (5). In all cases reported (3,5,6), the method involves the following steps 1) generation of the nitrating agent (presumably acetyl nitrate) by stirring finely ground copper nitrate with acetic anhydride at 0°C for 15 min…”
Section: Chromium (I Ii)mentioning
confidence: 99%
“…Metal 1,3-diketone systems behave as sensitive heterocycles possessing at least some aromatic character. Holm and cotton 15 have expressed doubt in such aromaticity but collman et al 16 and other workers have recognized their quasi-aromatic character and have reported electrophilic substitution reactions in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Forsch. 6, 479 (1966) (3) oder Methylferrocen-a-carbonsaure hinsichtlich der Ursache der optischen Aktivitiit Bhnlich sind.…”
unclassified